2006
DOI: 10.1080/14768320500422683
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use, time perspective and risk perception: Evidence of a moderating effect†

Abstract: This study explores the relationship between time perspective (TP), cannabis use and risk perceptions associated with this substance. A sample of French students (n ¼ 198) were provided with a valid French version of the Zimbardo Time Perspective Inventory (ZTPI) scale. Risk perceptions linked to cannabis consumption were evaluated from a list of 22 items referring to different risks. Respondents were asked to declare how frequently they consumed this substance. Data analysis was based firstly on ZTPI scores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 40 publications
6
55
0
4
Order By: Relevance
“…Also, while Kahle and Berman (1979) and Bentler and Speckart (1979) found support for attitudes predicting alcohol consumption, Johnson (1988) found no such evidence. The time perspective also moderated the link between marijuana use and risk perceptions (Apostolidis, Fieulaine, Simonin, & Rolland, 2006), and for example, the present-hedonistic dimension was positively associated with substance use (Keough et al, 1999), while future orientation was positively correlated with health responsibility (Hamilton et al, 2003) and negatively with substance use (Keough et al, 1999).…”
Section: Attitudes Risk Perception and (Il)licit Substance Usementioning
confidence: 99%
See 1 more Smart Citation
“…Also, while Kahle and Berman (1979) and Bentler and Speckart (1979) found support for attitudes predicting alcohol consumption, Johnson (1988) found no such evidence. The time perspective also moderated the link between marijuana use and risk perceptions (Apostolidis, Fieulaine, Simonin, & Rolland, 2006), and for example, the present-hedonistic dimension was positively associated with substance use (Keough et al, 1999), while future orientation was positively correlated with health responsibility (Hamilton et al, 2003) and negatively with substance use (Keough et al, 1999).…”
Section: Attitudes Risk Perception and (Il)licit Substance Usementioning
confidence: 99%
“…Respondents' gender and age were taken into account since they were usually significantly related to (il)licit substance use and to attitudes toward its use, as well as perception of risk associated with (il)licit substance use (e.g., Apostolidis et al, 2006;Roberts, 2012 …”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…Furthermore, extreme patterns of temporal biases might negatively affect health-related behaviors. For example, individuals who are strongly biased toward the present might not consider the future consequences of their acts by decreasing risk perception of behaviors such as smoking, substance use, or physical inactivity (e.g., Adams & Nettle, 2009;Apostolidis, Fieulaine, Simonin, & Rolland, 2006;Boyd & Zimbardo, 2005;Daugherty & Brase, 2010). The relevance of a biased TP in abnormal psychological functioning has also been suggested by several authors indicating that TP could be considered a core feature of some psychiatric disorders such as depression and suicidal ideation (Laghi, Baiocco, D'Alessio, & Gurrieri, 2009;van Beek, Berghuis, Kerkhof, & Beekman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of , which postulate that TP consists of five factors based on orientation and attitudes towards timeframes, several studies have shown that present orientation, in a hedonistic and sensation-seeking attitude, and future orientation, in a planning and goal-oriented attitude, are the most predictive factors in health behaviors, and in substance use (Keough, Zimbardo & Boyd, 1999;Apostolidis, Fieulaine, Simonin & Rolland, 2006). While individuals focused on future time perspective (FTP) are more likely to engage in health protective behaviors and to avoid risky ones, individuals predominantly possessing a present hedonistic time perspective (PHTP) are more likely to adopt risky behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%